2014
DOI: 10.31899/pgy10.1020
|View full text |Cite
|
Sign up to set email alerts
|

Provision of adolescent reproductive and sexual health services in India: Provider perspectives

Abstract: Chapter 1 Introduction 1 Chapter 2 Capacity building exposure of health care providers for adolescent friendly health service delivery Chapter 3 Provider perspectives on the provision of sexual and reproductive health information, counselling and services to adolescents and youth Chapter 4 Provider interaction with adolescents and youth Chapter 5 Provider perspectives on barriers to providing services to adolescents and youth Chapter 6 Summary and recommendations References Authors List of investigators iv Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Of 25 intervention studies, eight focused on intervention for female sex workers, two targeted injectable drug users and alcoholics and 1 targeted pregnant women. One study discussed the providers’ perspective on adolescent-friendly health services [ 61 ]. We found one study which examined the correlates of health-seeking behaviour [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 25 intervention studies, eight focused on intervention for female sex workers, two targeted injectable drug users and alcoholics and 1 targeted pregnant women. One study discussed the providers’ perspective on adolescent-friendly health services [ 61 ]. We found one study which examined the correlates of health-seeking behaviour [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study discussed the providers' perspective on adolescent-friendly health services [61]. We found one study which examined the correlates of health-seeking behaviour [61]. About ten were single intervention PLOS ONE studies, while the remaining 15 were multiple component intervention studies.…”
Section: Health-seeking Behaviour and Interventions To Prevent Sti/hivmentioning
confidence: 99%
“…Even programmes implemented in community settings tend to attract the richer and the more educated segments of girls in the communities (Acharya et al, 2009), suggesting the need for adopting measures to reach the most vulnerable girls. Similarly, although programmes that facilitate adolescents' access to sexual and reproductive health counselling and services-overwhelmingly conducted by the health department-are expected to meet the needs of different categories of adolescents, they tend to focus largely on females, exclude unmarried adolescent girls and reach out to married adolescent girls only after they have proven their fertility (Jejeebhoy et al, 2014;Santhya et al, 2014;Jejeebhoy and Santhya, 2011;Santhya et al, 2007). Clearly, there is a need to sensitise and build the skills of healthcare providers to respond to the needs of all categories of adolescents, including the unmarried.…”
Section: Background and Rationalementioning
confidence: 99%
“…Previous studies in India have shown that parents themselves are not fully informed about sexual and reproductive matters (Jejeebhoy and Santhya, 2011;Jejeebhoy et al, 2014). In our survey with mothers and fathers, we included several questions to assess their awareness of sexual and reproductive matters, including physical and behavioural changes associated with adolescence, sex-and pregnancy-related matters, legal minimum age at marriage, contraception, sexually transmitted infections, and HIV/AIDS.…”
Section: Parental Awareness Of Sexual and Reproductive Mattersmentioning
confidence: 99%